A comparison of Glucagon-like peptide-1 receptor agonists on weight change, side effects, and quality of life in Kuwait - Alali, Saleh; Al-Otaibi, Wed; Ashodian, Karen; Achour, Nour; Almulla, Aishah; Mutlaq, Hessa (Frontiers in Nutrition, 2025)
IntroductionAn estimated 74.6% of Kuwaiti adults are classified as overweight or obese. As a result, Glucagon-like peptide 1 receptor agonists (GLP-1 RA) injections such as, Semaglutide, Liraglutide, and Tirzepatide have become an increasingly popular intervention for weight loss. However, no research has been published on the use of GLP-1 RA injections in Kuwait.MethodsA cross-sectional study using an online survey was conducted between February and May 2024. Adults in Kuwait who have taken or are currently on GLP-1 RA injections were recruited. The questionnaire collected demographic and clinical data, including weight-loss, side-effects, and quality of life.ResultsIn this sample of N = 486, Tirzepatide users (N = 132; 27.8%) reported significantly higher monthly and annual weight-loss (4.76 ± 2.82 kg/month; 8.48 ± 4.04 kg/year), and greater satisfaction (88%) and improved quality of life (60%) compared to both Semaglutide (N = 181; 37.2%) and Liraglutide (N = 152; 31.3%), respectively. Side-effects varied: Tirzepatide users experienced more belching while Liraglutide reported higher anxiety levels and switching GLP-1 RA medication. No significant differences were found in BMI, following a diet, or compliance to treatment across the different GLP-1 RA groups.DiscussionThis study highlights the varying effectiveness and tolerability of GLP-1 RAs for weight loss in Kuwait, with Tirzepatide showing the highest satisfaction and weight loss. Liraglutide users experienced more anxiety and medication switches, while Semaglutide users had moderate outcomes. Despite their benefits, GLP-1 RAs face challenges in long-term adherence due to side effects and cost.